ZIKV Teratogenesis: Clinical Findings in Humans, Mechanisms and Experimental Models - Russo, Fabiele B.; Toledo, Carmen M.; Tocantins, Fernando R.; Souza, Giovanna V.; Beltrão-Braga, Patricia C. B. (Frontiers in Virology, 2022)
Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) from the Flaviviridae family, first isolated from the Rhesus monkey in 1947 in Uganda. ZIKV is transmitted by mosquito bites, but vertical and sexual transmissions have also been reported. ZIKV infection during pregnancy causes malformation in the developing fetus, especially Central Nervous System (CNS) damages, with a noticed microcephaly, making ZIKV be recognized as a teratogenic agent and the responsible for Congenital Zika Syndrome (CZS). However, it is still a short time since CZS was first reported. Consequently, ZIKV pathogenesis is not entirely elucidated, especially considering that affected children are still under neurodevelopment. Here, we will explore the current knowledge about ZIKV teratogenesis focusing on neurological clinical findings in humans, mechanisms, and experimental models used to understand ZIKV pathophysiology.